Assessment of mechanical rock alteration caused by CO2–water mixtures using indentation and scratch experiments. (February 2016) - Sun, Yuhao; Aman, Michael; Espinoza, D. Nicolas
Graphical abstract: Highlights: CO2 -altered rocks are characterized via micro-indentation and -scratch tests. Sedimentary rocks from Crystal Geyser, a natural CO2 seepage site, are examined. Results show significant reduction in hardness and fracture toughness. The procedure facilitates quick identification of facies susceptible to CO2 -alteration. Abstract: CO2 injection into geological formations disturbs the geochemical equilibrium between water and minerals. Thus, some mineral phases are prone to dissolution and precipitation with ensuing changes of petrophysical and geomechanical properties of the host formations. Chemically-assisted degradation of mechanical properties can endanger the structural integrity of the storage formation and must be carefully studied and considered to guarantee safe long-term trapping. Few experimental data sets involving CO2 alteration and mechanical testing of rock samples are available since these experiments are length, expensive, and require specialized equipment and personnel. Autoclave experiments are easier to perform and control but result in a limited "skin depth" of chemically-altered zone near the surface of the sample. This article presents the validation of micro-indentation and micro-scratch tests as efficient tools to assess the alteration of mechanical properties of rocks geochemically altered by CO2 –water mixtures. Results from tests on sandstone and siltstone from Crystal Geyser, Utah naturally altered by CO2 -acidified water show that mechanical parameters measured with indentation (indentation hardness, Young's modulus and contact creep compliance rate) and scratching (scratch hardness and fracture toughness) consistently indicated weakening of the rock after CO2 -induced alteration. Decreases of measured parameters vary from 14% to 87%. Experimental results and analyses show that micromechanical tests are potentially quick and reliable tools to determine the change of mechanical properties of rocks subject to exposure to CO2 -acidified water, particularly in well-controlled autoclave experiments. Measured parameters are not intended to provide inputs for coupled reservoir simulation with geomechanics but rather to inform the execution of larger scale tests investigating the susceptibility of rock facies to chemical alteration by CO2 –water mixtures. Recognizing this susceptibility of rock facies of CO2 geological storage target formations is critical to controlling undesired emergent behavior associated with CO2 sequestration.